Influence of Spatial Ability Levels on the Performance and Attitude of Physics Students - Adebisi, Thomas Ajibade; Feyijimi, Taiwo (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
The concept of spatial ability has been viewed within the boundary of technology and engineering by many researchers and education experts undermining its relevance to Physics at the secondary schools level. Spatial ability gives a wider ability to the use of higher order thinking skills which are accounted valuable for analysis, synthesis and evaluation needed in solving problems and has the tendency to influence students’ attitude. Therefore,   the study examined the influence of spatial ability levels on the performance and attitude of Physics students in public secondary schools in Osun State, Nigeria. A descriptive survey design was used for the study. The population for the study consisted of all the students in public secondary schools in four Local Government Areas (LGAs) of Ife in Osun State of Nigeria. A representative sample of 270 Physics students was selected using multi-stage sampling technique. Three instruments used for data collection are: Adapted Spatial Ability Test (ASAT), Performance Test in Physics (PTP) and Students’ Attitude Physics Questionnaire (SAPQ). Content validity of the three instruments was ensured by experts’ judgments. The reliability coefficient of 0.75, 0.85 and 0.82 were obtained for ASAT, PTP and SAPQ respectively. The results of the study classified students’ spatial ability to low, average and high levels and  many students had low spatial ability. The results of the study further showed that that there is statistically significant influence of spatial ability levels on the performance of physics students in the study areas.  The finding showed that there is no statistically significant influence of spatial ability levels on attitude of students towards Physics in the study areas. Consequently, it was recommended that there should be ongoing research on spatial ability to provide information for physics teachers and that Physics students should be encouraged to take lesson on various spatial ability activities.